Selecting organic desulphurization additives in flue gas desulphurization process. Issue 18 (16th September 2016) - Lv, Lina; Yang, Jianbin; Shen, Zhigang; Zhou, Yanbo; Lu, Jun
ABSTRACT: In order to find the rules of selecting organic desulphurization additives, eight kinds of organic acids with different pKa values, carbon chain lengths, and functional groups were discussed. As a result, three screening rules can be obtained for selecting organic desulphurization additives: firstly, the pKa value of organic acid should be between 4.21 and 4.83; then short carbon chain was better for SO2 removal; finally, organic acid with functional group was better than linear chain. Moreover, organic acids increased the desulphurization efficiency by promoting the oxidation of SO3 2− and accelerating the gas–liquid mass transfer and dissolution rate of SO2 .